Marketing + internet = e-commerce: opportunities and challenges - Pedro Barrientos Felipa (Revista Finanzas y Política Económica, 2017)
Despite only a short time passing since the Internet started to be used, it is clear today that it is producing significant changes in business. As this article highlights, this is only the beginning, since, for example, changes are being introduced to the way of life at home and at the office. For this reason, studies will continue to be carried out in order to better understand the impact and role of the Internet on the process of globalization. Currently, there is a new reality and many activities are replaced, including marketing, which now requires a new type of professionals and a new way of doing things. Management faces a challenge regarding information: what previously was scarce is now abundant and unordered. The future of business depends on the extent companies take advantage of the Internet. In this line, the article seeks to present the contribution of the Internet to the business sector and, consequently, to national economy. Similarly, it aims to explore the qualities that make the Internet attractive for business strategy, especially the benefits that companies must generate, not only expect. Finally, it seeks to expose the actions that companies must take, by making the most of the Internet, to improve cost productivity and to position their product or to strengthen it, while generating greater profits for the shareholders.